Features of digital management of modern economy - F. F. Sharipov; M. A. Dyakonova; M. Xu (Вестник университета)
The authors analyze the state of development of the digital economy, explore the changes and consequences of the impact of the rapidly developing digital economy on the national one from a managerial point of view. The network effect allows the “profit scaling” Internet model to form the dominant market economy and cross-border economy of scale quickly, strengthening the market position of the modern enterprise. Digitalisation brings not only enormous benefits to economic development, but also risks. The role of the state in improving the business ecosystem in the digital economy is increasing as a result of digital transformation. In the course of the research, the authors propose a number of directions of digital management in the modern economy. Among them are the formation of a methodology system for measuring and evaluating digital transformation; the disclosure of the value of a digital platform and the creation of a supervisory mechanism with multiple joint management; the promotion of digital innovation and the study of regulatory methods compatible with the development of new business formats; the improvement of laws and regulations and the creation of a legal digital economy management system; the use of the potential of big data to increase the level of digital governance, as well as strengthening international exchanges and cooperation, creation of a joint international digital economy management system.